EFFECT OF 2, 4-DICHLOROPHENOXYACETATE ON THE FORMATION OF PARANODULES ROOT IN DURUM WHEAT (Triticum durum Desf.) INOCULATED WITH Azospirillum brasilense ISOLATED IN RHIZOSPHERE OF WHEAT IN ALGERIA (Sciences & Technologie. C, Biotechnologies, 2012)
Several studies have shown that PGPR have beneficial effects on plants, these rhizobacteria may provide the plant with nitrogen as ammonium by their associations with legumes and some grasses. The strains of Azospirillum brasilense isolated before in rhizosphere of durum wheat, these strains can fix nitrogen improved by nitrogen content in leaves and total chlorophyll. The strains can colonized the durum wheat roots (Triticum durum Desf.) inocultated by formation of paranodules in roots induced by 2.4-D.These bacteria have also effect to improve growth yield these result was obtained by determination of thousand seeds weight.